Basic Approach for Design of Dual Band Microstrip Patch Antenna for Wi-Fi Application - Soojey Deshpande, Sneha Salvekar, Swati Joshi, Sharad Jagtap (Mathematical Statistician and Engineering Applications, 2022)
This paper presents a Dual band microstrip patch antenna for wireless communication. In its most basic form, a micro strip patch antenna consists of a Radiating patch on one side of a dielectric substrate which has a Ground plane on the other side .The patch is generally made of Conducting material such as copper and can take any Shape. A rectangular structure patch is used as the main Radiator. There are several advantages of this type of broadband Antenna, such as planar, small in size, simple in structure, low in Cost, and easy to be fabricate, thus attractive for practical applications. This rectangular micros trip patch antenna is designed for wireless communication Wi-Fi application that works at 2.4GHz.